An Introduction to Systems Thinking and its Application to Dentistry - Charles S. Czerepak (Taylor & Francis Group, 2024)
The discipline of systems thinking was developed to study and predict outcomes of large multicomponent systems. It provides a lens to examine complex problems, such as global warming or population health. This article applies the basic tenets of systems thinking to the practice of dentistry, looking specifically at patient safety and quality improvement. Using a systems view of the dental office; an argument is made for the development of a quality initiative through the creation of a mechanism for non-discoverable adverse event reporting. This would create a resource for dentists to learn from past adverse events and prevent them from happening again.